From Market Insight to Business Triumph: Unraveling the Role of Market Orientation in Enhancing MSMEs Performance - M. Lail Cahya Ulum; Agusty Tae Ferdinand; Fadel Wirawan Gunaldi; Nur Arifah (Khazanah Sosial, 2023)
This study aims to analyze the role of market orientation on performance in MSMEs in Semarang City. The research method used is quantitative. The object of research is SMEs in the city of Semarang. By using a non-probability sampling technique, namely convenience/accidental sampling, 200 samples were taken from 11,910 MSMEs. Data collection method using a questionnaire with a numerical scale. This research found that competitive advantage can be achieved by adopting market orientation, which involves customer orientation by understanding what customers want and need, competitor orientation by analyzing the strengths and weaknesses of competitors that can be leveraged by the company, and inter-functional coordination to develop strategies based on the gathered information. Marketing capabilities also play a crucial role in shaping competitive advantage. Marketing capabilities can develop and deliver superior value to customers by leveraging existing resources. Competitive advantage, market orientation, and marketing capability play a partial role in enhancing their business performance. Business performance is the goal of every organization. It is considered the core of strategic management, and therefore, most of their efforts are directed towards improving business performance. Companies can pay attention to important factors that can influence business performance. In this study, it was found that by focusing on competitive advantage, market orientation, and marketing capability, companies can enhance their business performance. The theoretical implication in this research is scientific development, while in practice, market orientation is a supporting factor that needs to be considered by MSME actors in order to achieve success.